Primary Ewing Family of Tumor Arising in the Ovary: A Case Report. (September 2019) - Li, Yi-Ping; Chang, Koping; Chen, Tom Wei-Wu; Lee, Shu-Ping; Chen, Chi-An; Cheng, Wen-Fang
Abstract : Ewing sarcoma and peripheral primitive neuroectodermal tumor constitute the Ewing family of tumors (EFT). EFTs primarily arising in the ovary are extremely rare. We report the case of a 22-yr-old nulliparous woman with a primary EFT in the ovary that initially presented as a 3-cm teratoma-like ovarian tumor, with rapid progression to a 15-cm-sized tumor with liver metastasis in 3 mo. The patient underwent suboptimal debulking surgery and salvage chemotherapy with vincristine, doxorubicin, and cyclophosphamide alternating with ifosfamide and etoposide. In conclusion, primary EFT in the ovary is extremely rare with highly aggressive behavior and poor outcome for metastatic disease. Demonstration of EWSR1 rearrangement, observed in a variety of soft tissue tumors, is very helpful in the diagnosis of EFT when interpreted on the basis morphology and immunohistochemistry. Abstract : Supplemental Digital Content is available in the text.